Identifikasi Fragmen Nisan Situs Kajang Batu di Museum Daerah Deli Serdang - Ifani, Aldita; Naldo, Jufri; Ali, Nasihudin (AHKAM, 2024)
This research aims to determine the shape and typology of the tombstones in the Kajang Batu cemetery. The method applied in this research is a qualitative method which is subjective by making direct observations of the objects studied. The Kajang Batu tombstone fragment is estimated to be 700 years old. The Kajang Batu tombstone fragment is an Acehnese type tombstone with a flat typology and does not contain many complicated motifs. In this case, many people must be involved so that these archaeological objects are maintained and preserved, one of which is the museum. Museums are a very suitable alternative for preserving cultural objects. Therefore, a museum's management of its collections can be a means for the public to obtain historical information in a unique and innovative way.